Quantification of Gender Bias and Sentiment Toward Political Leaders Over 20 Years of Kenyan News Using Natural Language Processing - Pair, Emma; Vicas, Nikitha; Weber, Ann M.; Meausoone, Valerie; Zou, James; Njuguna, Amos; Darmstadt, Gary L. (Frontiers in Psychology, 2021)
Background Despite a 2010 Kenyan constitutional amendment limiting members of elected public bodies to